Modified Legos is Effective in Stimulating Development on Pre-School Children - Nopi Nur Khasanah; Atina Mustafidah; Herry Susanto (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2018)
Background: Optimizing pre-school children development can be performed through stimulation with play activities. Interesting games able to motivate children actively to follow the rules of the designed game. Objective: This study aimed to analyze the effect of modified lego games on the development of pre-school children. Method: The research design of this study was Pre experimental One Group Pre-Post Test Design with the number of 17 respondents. Data analysis used marginal homogeneity test. Results and discussion: The number of children who had 'normal development' category had increased significantly from 52.9% (pre- test) to 76.5% (post-test). Bivariate analysis showed that there was ρ-value of 0.025 (<0.05). Games need to be modified to make it more attractive to children and hope that able to stimulate all aspects of development. Conclusion: This study shows a significant effect of modified lego games on the development among pre-school children.